In situ detection of the protein corona in complex environments. Issue 1 (December 2017) - Carril, Monica; Padro, Daniel; del Pino, Pablo; Carrillo-Carrion, Carolina; Gallego, Marta; Parak, Wolfgang
Abstract Colloidal nanoparticles (NPs) are a versatile potential platform for in vivo nanomedicine. Inside blood circulation, NPs may undergo drastic changes, such as by formation of a protein corona. The in vivo corona cannot be completely emulated by the corona formed in blood. Thus, in situ detection in complex media, and ultimately in vivo, is required. Here we present a methodology for determining protein corona formation in complex media. NPs are labeled with19 F and their diffusion coefficient measured using19 F diffusion-ordered nuclear magnetic resonance (NMR) spectroscopy.19 F diffusion NMR measurements of hydrodynamic radii allow for in situ characterization of NPs in complex environments by quantification of protein adsorption to the surface of NPs, as determined by increase in hydrodynamic radius. The methodology is not optics based, and thus can be used in turbid environments, as in the presence of cells. In situ detection of protein coronas is usually performed via optical methods, but light scattering may hamper these measurements. Here, the authors use diffusion NMR techniques to characterize protein corona formation on19 F-labeled nanoparticles in blood and other complex media.